Real Wages, Employment, and the Phillips Curve - Sumner, Scott; Silver, Stephen (Journal of Political Economy, 1989)
A recent study by Bils found real wages to be procyclical, contradicting previous findings by Geary and Kennan, who found no consistent relationship, and Neftci, who found countercyclical movements in real wages. These studies differed in both methodology and sample period. In this study, we found that real wages were either procyclical or countercyclical depending on the sample period chosen. Employment changes generated by aggregate supply shocks were associated with procyclical real wage movements, while during years dominated by shifts in aggregate demand, real wages were highly countercyclical.